Infrared spectroscopic study of the coil-helix transition of highly concentrated gelatin formulations - Polyak, Fabian; Reich, Gabriele (European journal of pharmaceutics and biopharmaceutics, 2019)
The aim of this study was to investigate the applicability of ATR-FTIR spectroscopy as an analytical tool to monitor the gel formation of highly concentrated gelatin formulations. Spectral changes induced by the coil-helix transition have been studied and related to the elasticity parameter G′ obtained by oscillatory rheology in simultaneous measurements. A principal component analysis of the amide I band allowed the evaluation of triple helix formation kinetics. It was found that the key frequencies of the amide I band at 1657 and 1612cm−1 represent the transition of the gelatin molecules from the random coil to the triple helical conformation in the emerging gel. A direct correlation between the conformation of the gelatin molecules and the gel elasticity was obtained for a commercially available pharmaceutical grade limed bone gelatin in concentrations between 20 and 40% w/w. The same was valid upon addition of small gelatin peptides or a helix inhibitor. No such correlation between triple helix content and G′ was found for limed bone gelatins of the same Bloom value but an asymmetric molecular weight distribution with extremely high fractions of high or low molecular weight components. This suggests that early gel elasticity is not solely linked to the triple helix nucleation. Hence, our results indicate that FTIR spectroscopy can be applied to gain a better understanding of the relationship between triple helix content and elastic gel properties of pharmaceutical gelatin capsule shell formulations.
Gesehen am 04.12.2019